2018
DOI: 10.1007/s40746-018-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Aerodigestive Approach to Chronic Cough in Children

Abstract: Purpose of review: Chronic cough is the most common presenting complaint in a pediatric aerodigestive clinic. The etiology of chronic cough is varied and often includes more than one organ system. This review aims to summarize the current literature for a multidisciplinary approach when evaluating a child with chronic cough. Recent findings: There is very little medical literature focused on a multidisciplinary approach to chronic cough. In the limited data available, multidisciplinary clinics have been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
7
0
3
Order By: Relevance
“…This is possibly expected considering the majority of our cohort is made up of surgically corrected congenital airway conditions predisposing to poor mucociliary clearance. 14,15 A wide range of prevalence of respiratory infections has been reported in different studies (11-48%) in cases of surgically managed OA and TOF in the first 5 years of life. 10,16 In our cohort, recent lower respiratory tract infections were noted in 21% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly expected considering the majority of our cohort is made up of surgically corrected congenital airway conditions predisposing to poor mucociliary clearance. 14,15 A wide range of prevalence of respiratory infections has been reported in different studies (11-48%) in cases of surgically managed OA and TOF in the first 5 years of life. 10,16 In our cohort, recent lower respiratory tract infections were noted in 21% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Having participated in many ADC scientific events, we have observed that our ADC approach to patient management is quite similar to that of other North American institutions. 6,18,19 The inherently heterogeneous presenting features, prior treatments, physical findings and diagnostic results of the ADC patient population warrants a tailored, and consequently heterogeneous approach, to management.…”
Section: Discussionmentioning
confidence: 99%
“…El hallazgo laringoscópico predominante de laringomalacia no debe pasarse por alto, ya que; al ser una patología estructural congénita puede ser una importante causa o comorbilidad de problemas de deglución, reflujo gastroesofágico, fallo para progresar y tos crónica (Naime et al, 2018). Esta patología es la más frecuente en las anomalías congénitas de la laringe y se considera que resolverá de forma espontánea en casi todos los casos.…”
Section: Nº De Pacientesunclassified
“…Las broncoscopias brindaron información importante respecto a la etiología de la sintomatología del paciente, como es el caso del hallazgo de bronquitis bacteriana recurrente. Tomando en cuenta que la bronquitis bacteriana prolongada es la primera causa de tos húmeda persistente en niños menores de 5 años, el diagnóstico microbiológico es fundamental para una mejor orientación terapéutica en función de la persistencia del proceso bronquial (Naime et al, 2018). Los patógenos más frecuentes evidenciados mediante cultivo de lavado broncoalveolar fueron muy similares a los reportados como principales entidades en otros estudios, por ejemplo, en el informe del Sistema Nacional de Salud de Michigan (Fracchia et al, 2018).…”
Section: Nº De Pacientesunclassified
See 1 more Smart Citation